2001
DOI: 10.1002/ajim.1075
|View full text |Cite
|
Sign up to set email alerts
|

Occupational cancer genetics: infrequent ras oncogenes point mutations in lung cancer samples from chromate workers

Abstract: Ras oncogenes activated by point mutations do not have a major role in the process of tumorigenesis of chromate-related lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In some cases, for example, in chromate-related lung cancer, no mutations in RAS genes were found. The reason that no mutations were detected in these chromate-related lung cancer samples is that almost all chromate lung cancers were proved pathologically to be of the small cell cancer type, in which RAS genes rarely mutate [57]. This is consistent with previous studies that reported infrequent RAS-genes mutations in the small cell cancer pathological type of lung cancer samples, while adenocarcinoma was the pathological type that showed a high percentage of mutated RAS genes [58].…”
Section: Ras Mutationssupporting
confidence: 91%
“…In some cases, for example, in chromate-related lung cancer, no mutations in RAS genes were found. The reason that no mutations were detected in these chromate-related lung cancer samples is that almost all chromate lung cancers were proved pathologically to be of the small cell cancer type, in which RAS genes rarely mutate [57]. This is consistent with previous studies that reported infrequent RAS-genes mutations in the small cell cancer pathological type of lung cancer samples, while adenocarcinoma was the pathological type that showed a high percentage of mutated RAS genes [58].…”
Section: Ras Mutationssupporting
confidence: 91%
“…Our previous studies have investigated the alterations of oncogenes, tumor suppressor genes, and DNA mismatch repair genes in lung cancer from chromate-exposed workers [6][7][8][9]. Our study demonstrated that LOH at the p16 locus (D9S161) was common not only in non-chromate lung cancer, but also chromate lung cancers (54% versus 78%) [8].…”
Section: Discussionmentioning
confidence: 54%
“…However, its genetic effects in humans are only partially understood. On the other hand, our previous study examined p53 and ras mutations, genetic instability, and the inactivation of hMLH1 expression in human chromate lung cancer [6][7][8][9]. Our previous study demonstrated that the loss of heterozygosity (LOH) at the 9p21 region (D9S161 marker) was more common in lung cancer patients with chromate exposure than in lung cancer patients without (78% versus 54%) [8].…”
Section: Introductionmentioning
confidence: 94%
“…27,28 There was no significant difference in loss of heterozygosity (LOH) at 3p between chromate-induced lung carcinomas and non-chromate-induced lung carcinomas. 13 In contrast, the frequency of RER in chromate-induced lung carcinomas (78.9%) was significantly higher than in non-chromate-induced lung carcinoma (15.4%).…”
Section: Discussionmentioning
confidence: 99%